(untitled) (Research, Society and Development, 2022)
The drying stage is the most relevant procedure in the industrial production of ceramic bricks, since the final quality of the product is directly related to the success of this operation. Knowledge of the material’s thermal and mass diffusivity facilitates mathematical modeling, which brings us a greater domain of the process. With this purpose, the drying of solid ceramic bricks with different percentages of diatomite tailings was experimentally carried out in an oven with forced air circulation. The experiments were performed based on a 2k experimental design with three factors: the drying temperatures (333 and 383 K), the homogenization time of the mixture (30 and 60 min), and the percentage of tailings (10 and 30%). From the results matrix, we applied the Levenberg-Marquardt algorithm to minimize the difference between the theoretical and the experimental drying and heating curves, thus obtaining the thermal and mass diffusivities. Still in possession of the results matrix, we applied a regression model in order to obtain an equation to estimate the diffusivity values. The drying and heating curves that were built from the estimated diffusivities showed good agreement with the experimental data, and were validated within a 99% confidence interval.